2009
DOI: 10.1177/1010539509352803
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety Prevalence and Affecting Factors Among University Students

Abstract: This study provides insight into the prevalence and correlates of anxiety among university students in Bursa, Turkey. A total of 4850 students participated in the study. Students completed Spielberger's State-Trait Anxiety Inventory, as well as a questionnaire designed to determine risk factors of anxiety. About 29.6% and 36.7% of the students in the study reported state and trait anxiety scores of more than 45 points, respectively. Controlling for gender and family socioeconomic status, the following characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
1
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 11 publications
3
23
1
7
Order By: Relevance
“…MEB'in istihdam politikaları nedeniyle birçok öğretmen adayı, henüz lisans öğreniminde yoğun olarak gelecek ve iş kaygısı yaşayabilmektedir. Yapılan bir çalışma eğitim ve mühendislik fakültelerinde öğrenim gören öğrencilerin, istihdam edilmede nispeten problem yaşamayan tıp fakültesi öğrencilerine göre daha fazla kaygılı olduklarını göstermektedir (Özen, Ercan, Irgil & Sığırlı, 2010). Öğretmen adaylarının yaşadıkları stresi sadece gelecek veya iş kaygısı ile açıklamak doğru olmayacaktır.…”
Section: Introductionunclassified
“…MEB'in istihdam politikaları nedeniyle birçok öğretmen adayı, henüz lisans öğreniminde yoğun olarak gelecek ve iş kaygısı yaşayabilmektedir. Yapılan bir çalışma eğitim ve mühendislik fakültelerinde öğrenim gören öğrencilerin, istihdam edilmede nispeten problem yaşamayan tıp fakültesi öğrencilerine göre daha fazla kaygılı olduklarını göstermektedir (Özen, Ercan, Irgil & Sığırlı, 2010). Öğretmen adaylarının yaşadıkları stresi sadece gelecek veya iş kaygısı ile açıklamak doğru olmayacaktır.…”
Section: Introductionunclassified
“…The State-Trait Anxiety Inventory (STAI) is one of the most widely used selfreport measures of anxiety in clinical and research settings [1] [40] [41], and has been found to be both reliable and valid [40]. The STAI clearly differentiates between the temporary condition of "state anxiety" which is a subjective fear experienced by an individual in a stressful situation [1] and the more general and long-standing quality of "trait anxiety" which is a predisposition of an individual to anxious living [1].…”
Section: Measurements Of Stress and Anxietymentioning
confidence: 99%
“…Gerwing [8] et al found that 38.5% of students (30.0% of males, 46.3% of females) self-reported that they suffered from some level of test anxiety throughout their university career. Test anxiety can lead to high levels of worry and physical discomfort [9], and disrupts a person's ability to think, perceive and learn [1]. A person suffering from anxiety usually experiences difficulty in concentrating, remembering materials, and establishing necessary relations among events or people [1].…”
Section: Introduction and Review Of Literaturementioning
confidence: 99%
See 2 more Smart Citations